Willingness to pay for community delivery of antiretroviral treatment in urban Tanzania: a cross-sectional survey. Issue 10 (23rd October 2020) - Geldsetzer, Pascal; Sauer, Alexander; Francis, Joel M; Mboggo, Eric; Lwezaula, Sharon; Sando, David; Fawzi, Wafaie; Ulenga, Nzovu; Bärnighausen, Till
Abstract: Community health worker (CHW)-led community delivery of HIV antiretroviral therapy (ART) could increase ART coverage and decongest healthcare facilities. It is unknown how much patients would be willing to pay to receive ART at home and, thus, whether ART community delivery could be self-financing. Set in Dar es Salaam, this study aimed to determine patients' willingness to pay (WTP) for CHW-led ART community delivery. We sampled ART patients living in the neighbourhoods surrounding each of 48 public-sector healthcare facilities in Dar es Salaam. We asked participants ( N  = 1799) whether they (1) preferred ART community delivery over standard facility-based care, (2) would be willing to pay for ART community delivery and (3) would be willing to pay each of an incrementally increasing range of prices for the service. 45.0% (810/1799; 95% CI: 42.7—47.3) of participants preferred ART community delivery over standard facility-based care and 51.5% (417/810; 95% CI: 48.1—55.0) of these respondents were willing to pay for ART community delivery. Among those willing to pay, the mean and median amount that participants were willing to pay for one ART community delivery that provides a 2-months' supply of antiretroviral drugs was 3.61 purchasing-power-parity-adjusted dollars (PPP$) (95% CI: 2.96–4.26) and 1.27 PPP$ (IQR: 1.27–2.12), respectively. An important limitation of this study is that participants all resided in neighbourhoods within the catchment area of the healthcare facility at which they were interviewed and, thus, may incur less costs to attend standard facility-based ART care than other ART patients in Dar es Salaam. While there appears to be a substantial WTP, patient payments would only constitute a minority of the costs of implementing ART community delivery. Thus, major co-financing from governments or donors would likely be required.